Is “Opting Out” Really an Answer? Schools, Militarism, and the Counter-Recruitment Movement in Post-September 11 United States at War - Tannock, Stuart (Social justice, 2005)
Part of a special issue on challenging corporate control of schools and communities. The writer critically examines the analytic framework that shapes most antiwar and counter-recruitment work in the U.S. He states that such work tends to be based upon the opt out principle whereby parents can sign a form requesting that their child's personal contact information not be handed over to the military by their high school, as is required by a provision in the No Child Left Behind Act. Suggesting that opting out is not the best way to strengthen and extend the reach of counter-recruitment work, he discusses alternative means of altering the structural and cultural forces that drive U.S. youth toward empire, violence, and war.